Conversion of furan derivatives for preparation of biofuels over Ni–Cu/C catalyst. Issue 11 (3rd June 2017) - Fu, Zhaolin; Wang, Ze; Lin, Weigang; Song, Wenli
ABSTRACT: Conversions of furfural and 5-hydroxymethylfurfural as model components in bio-oil were investigated over Ni–Cu/C catalyst with formic acid as hydrogen donor in isopropanol solvent to produce biofuels. The effects of reaction temperature, feed ratio, and reaction time were studied. A high yield of 2-methylfuran up to 91 mol% was obtained from furfural in 8 h at 200°C, and under same conditions 80 mol% yield of 2, 5-dimethylfuran could also be obtained from 5-hydroxymethylfurfural in 6 h. The results verified the catalyst performance and the availability of the reaction conditions for producing biofuels from furan derivatives.